Characterization and discrimination of milk volatiles from donkey fed different roughages using GC-IMS - Du, Xinyi; Zhao, Yan; Ding, Lu; Huang, Fei; Ren, Wei; Ma, Zongjie; Zhu, Mingxia; Liu, Guiqin; Khan, Muhammad Zahoor; Wang, Changfa; Zhou, Miaomiao; Li, Mengmeng (Frontiers in Nutrition, 2025)
IntroductionThe flavor is one of the important qualities of milk, which the effect of roughage on the composition of volatile compounds (VOCs) in donkey milk is unclear.MethodsThis study comprehensively analyzed the VOCs of milk from donkeys fed with corn straw (G1), wheat hulls (G2), or wheat straw (G3) using GC-lMS combined with multivariate analysis.ResultsA total of 43 VOCs were identified in donkey milk including 27.91% esters, 25.58% ketones, 18.60% aldehydes, and 16.28% alcohols. The levels of esters and aldehydes were significantly higher in the G1 group than in the G2 and G3 groups, whereas the opposite was true for alkenes. The 13 VOCs with relative odor activity value >1 were the major characteristic flavor compounds of donkey milk, mainly thiocyanic acid methyl ester, acetic acid ethyl ester, and hexanal. The VOCs in the milk from donkeys fed with corn straw (G1), wheat hulls (G2), or wheat straw (G3) were well differentiated using two-dimensional, difference, three dimensional spectra, and fingerprint gallery plots. A total of 23 different VOCs were identified as potential markers to distinguish the milk of donkeys fed with different roughage, including 2-acetylpyrrole, benzaldehyde-dimer, and hexanal-monomer.ConclusionOur study indicates that the VOCs in donkey milk are influenced by different roughage fed to donkeys and provided a theoretical basis for the regulation of VOCs in donkey milk by roughages.